Moleeular confirmation of sympatric populations of Anopheles messeae and Anopheles atroparvus overwintering in Kent, southeast England. Issue 13 (2002) - Linton, Yvonne-Marie; Harbach, Lisa Smithand Ralph E.
No abstract available